Hematological values of the yellow-spotted river turtle (Podocnemis unifilis) in two seasons in a zoo in Iquitos, Peru - Carlos Erazo, Nancy (2020)
The aim of this study was to determine blood values of the yellow-spotted river turtle (Podocnemis unifilis) in two seasons in a zoo in Iquitos, Peru. The zoo has a population of 80 turtles of this species. Thirty turtles were used in the study (18 males, 12 females). Blood samples were taken in winter (February) and summer (July) and were analysed were analysed using Neubauer's camera and the dilutor Natt & Herrick. The season of the year influenced the blood values, increasing the number of erythrocytes and azurophils in summer, and of lymphocytes and thrombocytes in winter.